Eye lens dosimetry for workers at Fukushima Daiichi Nuclear Power Plant—2: Field study using humanoid phantoms. (June 2020) - Tsujimura, Norio; Hoshi, Katsuya; Aoki, Katsunori; Yoshitomi, Hiroshi; Tanimura, Yoshihiko; Yokoyama, Sumi
Abstract: We performed a field study of eye lens dosimetry for workers involved in the decommissioning operation at the Fukushima Daiichi Nuclear Power Plant. In this study, humanoid phantoms equipped with different personal dosemeters were placed at selected locations in the workplace. The experiment showed that H p (3) at the head is about 20% higher than H p (10) (or H p (3)) at the trunk. This level of dose gradient is generally interpreted as being "almost uniform" in radiological control; therefore, tasks conducted in open areas with such relatively small dose gradients (~1.2) will not require specific monitoring with eye lens dosemeters, except when the eye lens dose approaches the dose limit. Highlights: Eye lens dosimetry study at the Fukushima Daiichi Nuclear Power Plant. Humanoid phantoms equipped with eye lens and whole-body dosemeters. Comparison of H p (3) at the head with H p (10) at the trunk.